Effects of age on match-related acceleration and deceleration efforts in elite soccer players - Lorenzo-Martínez, M.; Corredoira, F. J.; Lago-Peñas, C.; López-Del Campo, R.; Nevado-Garrosa, F.; Rey, E. (International Journal of Sports Medicine, 2021)
The aim of this study was to examine the effects of chronological age on acceleration and deceleration match performance in professional soccer players. A total of 5317 individual match observations were collected on 420 professional players competing in the Spanish LaLiga during the 2018-2019 season, using a multiple-camera computerised tracking system (TRACAB; ChyronHego, Melville, NY, USA). Players were classified using a k-means cluster analysis into four different age groups: 17-23 years, 24-27 years, 28-30 years, and 31-38 years. Linear mixed models were adjusted to compare the players` match performance according to their age group and playing position (central defenders, external defenders, central midfielders, external midfielders, and forwards). The results showed that players aged between 31-38 years performed a significantly less total number of accelerations (ES=0.30-0.48) and decelerations (ES=0.29-0.49) in comparison with younger players. These age-related physical performance declines were more pronounced among central defenders, central midfielders, and forwards. However, no significant effects were obtained for players` maximum acceleration and deceleration capacities. The current findings provide useful information for coaches and strength and conditioning specialists to better understand the effects of age on players` physical performance and to develop age-tailored training programs.